Cefquinome Controlled Size Submicron Particles Precipitation by SEDS Process Using Annular Gap Nozzle. (3rd July 2017) - Xiao, Kefeng; Wang, Weiqiang; Hu, Dedong; Qu, Yanpeng; Hao, Zhihui; Wang, Leilei
Abstract : An annular gap nozzle was applied in solution enhanced dispersion by supercritical fluids (SEDS) process to prepare cefquinome controlled size submicron particles so as to enhance their efficacy. Analysis results of orthogonal experiments indicated that the concentration of solution was the primary factor to affect particle sizes in SEDS process, and feeding speed of solution, precipitation pressure, and precipitation temperature ranked second to fourth. Meanwhile, the optimal operating conditions were that solution concentration was 100 mg/mL, feeding speed was 9 mL/min, precipitation pressure was 10 MPa, and precipitation temperature was 316 K. The confirmatory experiment showed thatD 50 of processed cefquinome particles in optimal operating conditions was 0.73  μ m. Moreover, univariate effect analysis showed that the cefquinome particle size increased with the increase of concentration of the solution or precipitation pressure but decreased with the increase of solution feeding speed. When precipitation temperature increased, the cefquinome particle size showed highest point. Moreover, characterization of processed cefquinome particles was analyzed by SEM, FT-IR, and XRD. Analysis results indicated that the surface appearance of processed cefquinome particles was flakes. The chemical structure of processed cefquinome particles was not changed, and the crystallinity of processed cefquinome particles was a little lower than that of raw cefquinome particles.